Neuromodulation in Psychiatry. - Hamani, Clement; Holtzheimer, Paul E.; Lozano, A. M. (Andres M.), 1959-; Mayberg, Helen S. (Helen Susan), 1956- (Wiley, 2015)
This is the first comprehensive and detailed reference work that focuses on neuromodulation strategies in psychiatry. Neuromodulation strategies are no longer confined to tertiary hospitals but are used in community practices and even by individual psychiatrists. Surgery for psychiatric disorders is one of the main advances in the field of functional neurosurgery.
Neuromodulation in Psychiatry includes chapters on the history of this controversial field and the ethics of modern usage of such techniques. Specific chapters are devoted to neuromodulation and surgical strategies used in psychiatry including transcranial magnetic stimulation, transcranial direct current stimulation, vagus nerve stimulation, direct cortical stimulation and deep brain stimulation. A chapter describes the basic principles of each technique, using figures and schematics to illustrate details for people who do not have personal experience of using these techniques. Another chapter then focuses on the results of clinical research, trials and applications for that strategy.
Encompasses basic principles, technical aspects and clinical applications including ethical considerations.
Clearly explains each technique with implications for clinical practice.
Presents evidence in a comprehensive summary suitable for all levels.
Allows psychiatrists to evaluate results obtained using such strategies and to make decisions regarding the best course of treatment for their patients.
An essential reference guide for psychiatrists, psychologists, neurosurgeons, neurologists and their respective trainees, Neuromodulation in Psychiatry covers all neuromodulation strategies now used or with potential use in psychiatry. It allows readers to evaluate the results obtained using such strategies, and to make informed decisions regarding the best course of treatment for their patients. --Book Jacket.
Transcranial magnetic stimulation; Transcranial direct current stimulation; Deep brain stimulation; Characterizing the effects of neuromodulation using MRI; Transcranial direct current stimulation; Transcranial magnetic stimulation; DBS; Optimizing individual treatment parameters using MRI; Neuromodulatory effects of MRI itself; Conclusions; Acknowledgements; References; CHAPTER 5 Nuclear medicine in neuromodulation; Introduction; Basic principles of PET; Gamma ray detection; What can PET measure?; Radiopharmaceuticals; Clinical research applications; Pathophysiology of psychiatric illness.
Major depressive disorder.
Print version record.
Keywords: Electroconvulsive therapy; Magnetic brain stimulation; Mental illness -- Treatment; Electroconvulsive therapy; Magnetic brain stimulation; Mental illness -- Treatment; Electronic books